Can a morphological description of the peritoneal carcinomatosis in advanced ovarian cancer add prognostic information? Analysis of 1686 patients of the tumor bank ovarian cancer - Nasser, Sara; Babayeva, Aygun; Braicu, Ioana; Richter, Rolf; Bilir, Esra; Chekerov, Radoslav; Muallem, Mustafa-Zelal; Pietzner, Klaus; Inci, Melissa-Guelhan; Sehouli, Jalid (Frontiers in Oncology, 2022)
Background: Peritoneal carcinomatosis in ovarian cancer is frequent and generally associated with higher stage and poorer outcome. The clinical features of peritoneal carcinomatosis are diverse and their relevance for surgical and long-term outcome remains unclear. We conducted this prospective study to describe intraoperatively the different features of peritoneal carcinomatosis(PC) and correlate them with clinicopathological features, progression-free(PFS) and overall survival (OS),. Methods: We performed a systematic analysis of all patients with documented intraoperative PC and a primary diagnosis of epithelial ovarian, tubal, or peritoneal cancer from January 2001 to September 2018. All data were evaluated by using the systematic tumour bank tool. Specific PC features included texture(soft-hard), consistency(coarse-fine or both), wet vs dry(PC with ascites vs. PC without ascites), and localization(diffuse-local). PC characteristics were then evaluated for correlation with age, FIGO-stage, histology, lymph-node involvement, grade, and presence of residual tumour at primary surgery. Moreover, the influence of PC characteristics on OS and PFS was analysed. Results: A total of 1686 patients with PC and primary epithelial ovarian cancer were included. Majority of the patients were characterized by diffuse PC(73.9%). The majority of peritoneal nodules were fine in texture (55.3%) and hard in consistency (87.4%). Moreover, 27.6% of patients had dry PC. Diffuse PC localization was significantly associated with higher FIGO-stage (p<0.001), high-grade (p=0.003) and serous tumours (p=0.006) as well as residual tumour as compared to local PC (p<0.001). Wet PC also significantly correlated with diffuse localization (p <0.001) and residual tumour as compared to dry PC (p<0.001). Coarse PC was significantly associated with residual tumour as compared to fine PC (p=0.044). All other PC features didn´t correlate with clinicopathological features. As for survival outcomes, diffuse peritoneal localization (p<0.001), wet PC (p<0.001), and additional lymph node involvement (p<0.001) were associated with lower OS and PFS rates. Other PC features did not significantly impact survival. Conclusion: Diffuse localization of peritoneal carcinomatosis was significant predictor of recurrence. Lower OS and PFS were associated with diffuse peritoneal localization, wet PC, and additional lymph node involvement. Further prospective trials are warranted with the inclusion of translational research aspects to better understand the different peritoneal carcinomatosis patterns.